Mineralogy of the Imalia Au-Sn-bearing polymetallic sulfide deposit, Mahakoshal belt, Central India - Tripathi, Shubham; Deb, Mihir (Journal of Asian Earth Sciences: X, 2022)
•Imalia is a polymetallic sulfide deposit in carbonate rocks intruded by porphyry dykes.•The deposit has compleX rare metal association in addition to gold and tin.•Vein ores host electrum, Bi/As sulfosalts, roquesite, idaite, cassiterite amongst others.•Invisible Au and Sn are structurally located in pyrite and arsenopyrite in vein type ores. The Au-Sn-bearing, polymetallic sulfide deposit at Imalia in the western part of Mahakoshal belt, Central India is hosted by recrystallized dolostone and subsidiary phyllitic dolostone. These host rocks are transected by shallow level intrusion of quartz porphyry dykes. There are two major NS trending ore zones (∼1.5 km cumulative length) and a subsidiary-one, confined to fractures and shears in the dolostones or along its contact with the intrusive dykes. Polyphase mineralization include: irregularly disseminated pyrite crystals of diagenetic/metamorphic origin, patchy to stringery Pb-Zn sulfide ores showing pervasive metamorphic fabric, dominant massive vein type pyrite-arsenopyrite ores with significant amounts of invisible gold and tin. Other ore minerals include cassiterite, molybdenite, wolframite and roquesite in a magnetite-rich oxidic halo, and electrum, enargite/luzonite, wittichenite, ourayite, eclarite, aikinite and idaite in the sulfidic veins. Some tentatively identified ore minerals in these veins include calaverite, proustite, famatinite, sakuraiite, and tenorite. Pyrite contains structurally located invisible gold as high as 17.6 ppm whereas arsenopyrite contains a maximum of 20–24 ppm Au. Pyrite also contains unusually high Sn (upto 2673 ppm). The mineralogical assemblage of rare phases and their paragenesis in the Imalia vein type ores reflect the high sulfur (log fS2 = −9 to −13 bar) and oxygen (logfO2 = −32 bar) fugacities at a temperature range of 350 °C to 250 °C (according to thermometric calculations) during their emplacement.